THE EFFECTIVENESS OF NUMBERED HEADS TOGETHER IN TEACHING READINGVIEWED FROM STUDENTSâ LOCUS OF CONTROL - Handoko, Muhamad Dini (JURNAL PEDAGOGY, 2013)
Abstract : This writing applied an experimental design. The population of the research was the eighth graders of Senior High School academic year of 2011/2012 consisting of three classes. Two out of the three classes, consisting of 40 students, were used as the sample using the technique of cluster random sampling. The experimental group was taught using the NHT strategy, while the control group using expository strategy. A questionnaire and test of reading were used to collect the research data. The result of analysis shows that NHT is proved as an effective teaching strategy to teach reading for the eighth grade. The effectiveness is affected by studentsâ level of Locus of Control.Key words: Numbered Heads Together (NHT), Expository Teaching Strategy, Locus of Control